A better way to improving the Quality of Head and Neck cancer Referral : A post- Covid reflection, data analysis and effect on service delivery. Issue 1 (January 2022) - Srinivasan, Jothi; Jones, Keith; Ly, Derek
Abstract : Introduction/Aims: The implementation of COVID lockdown on 26 March 2020, led to a significant drop in urgent cancer referrals. This study looks at the quality of urgent cancer referrals and the impact of pandemic on the proportion of referrals to Royal Derby Hospital Head and Neck Unit with an eventual diagnosis of cancer. The data emphasises the need for us to look at the ways to improve the cancer referral pathway and service delivery. Materials and Methods: Retrospective electronic case note review was performed of urgent cancer referrals from general practitioners and general dental practitioners to Oral and Maxillofacial Surgery and Ear, Nose and Throat Head & Neck Cancer service at the Royal Derby Hospital. Results/Statistics: A total of 661 appointments were performed between 8 January 2020 and 30 June 2020 at the Head and Neck Cancer service. 98.9% of appointments pre-lockdown were seen face-to-face. This reduced to 62% of appointments post-lockdown. Only 60.1% of patients were informed of their urgent cancer referral pre-lockdown. 55.1% of patients were informed post-lockdown. The proportion of referrals with an eventual diagnosis of cancer increased from 6.4% to 13.3% in the 3 months following lockdown. Conclusions/Clinical Relevance: The outcome of this study showed an increase in proportion of referrals diagnosed with cancer despite reduced face to face appointments .This demonstrates the need to improve the quality of urgent cancer referrals including provision of the referral pathway information to patients and re-evaluate the current referral system criteria .This would be with a specific focus on educating the General Dental and Medical practitioners and reconfiguraton of hospital services.